1999
DOI: 10.1021/ja9829822
|View full text |Cite
|
Sign up to set email alerts
|

C2-Symmetric Copper(II) Complexes as Chiral Lewis Acids. Scope and Mechanism of Catalytic Enantioselective Aldol Additions of Enolsilanes to (Benzyloxy)acetaldehyde

Abstract: C 2-Symmetric bis(oxazolinyl)pyridine (pybox)−Cu(II) complexes have been shown to catalyze enantioselective Mukaiyama aldol reactions between (benzyloxy)acetaldehyde and a variety of silylketene acetals. The aldol products are generated in high yields and in 92−99% enantiomeric excess using as little as 0.5 mol % of chiral catalyst [Cu((S,S)-Ph-pybox)](SbF6)2. With substituted silylketene acetals, syn reaction diastereoselection ranging from 95:5 to 97:3 and enantioselectivities ≥95% are observed. Investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
170
2
6

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 400 publications
(186 citation statements)
references
References 59 publications
8
170
2
6
Order By: Relevance
“…However, it was both encouraging and disappointing to find that although the reactivity was indeed enhanced significantly, no enantioselectivity was observed with most of these chiral catalysts. On the other hand, numerous enantioselective addition reactions with chiral copperbis(oxazoline) box complexes have been described during the past two decades (59)(60)(61). Therefore, we decided to try chiral bis(oxazolinyl) ligands in our reaction and found that the desired enantioselective addition product was formed with a low enantioselectivity by using bidentate box 1 and 2 with CuBr complex as catalysts in water (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was both encouraging and disappointing to find that although the reactivity was indeed enhanced significantly, no enantioselectivity was observed with most of these chiral catalysts. On the other hand, numerous enantioselective addition reactions with chiral copperbis(oxazoline) box complexes have been described during the past two decades (59)(60)(61). Therefore, we decided to try chiral bis(oxazolinyl) ligands in our reaction and found that the desired enantioselective addition product was formed with a low enantioselectivity by using bidentate box 1 and 2 with CuBr complex as catalysts in water (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Williams has reported that heterochiral [Co(Sub-pybox) 2 ] was formed selectively when Sub was Ph; however, mixtures of homo-and heterochiral complexes were formed when Sub was Me and Bz.…”
mentioning
confidence: 99%
“…Evans and Jørgensen have both observed that, even using a M:1 ratio of 1:1, racemic 1 gave the near insoluble, catalytically inactive complex [M(1R)(1S)] 2+ . 3,4 Williams has reported that heterochiral [Co(Sub-pybox) 2 ] was formed selectively when Sub was Ph; however, mixtures of homo-and heterochiral complexes were formed when Sub was Me and Bz. 5 This diastereoselectivity was explained by the avoidance of steric interference between Ph-substituents on different ligands in the heterochiral complex and the possibility of favorable ³-stacking interactions between the Ph-substituents of one pybox ligand with the pyridine ring of another pybox ligand.…”
mentioning
confidence: 99%
“…Although the hydrolysis-prone silyl ketene acetal derived from ester 13 could not be obtained in synthetically useful levels of purity in our hands, silyl ketene thioacetal 20 (Z:E=99:1), derived from thioester 14 in 95% yield, was more stable than the corresponding ester derivative, 26 and could be purified on Florisil. The stereochemistry of the major isomer was verified by 1 H NOE correlation (0.3%) between Si(CH 3 ) 3 and the methine proton in 20.…”
Section: Aldol Reactionmentioning
confidence: 75%